1975
DOI: 10.1002/bjs.1800620214
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of one layer and two layer techniques for colorectal anastomosis

Abstract: In a randomized prospective clinical trial and layer and two layer techniques have been compared in 92 patients undergoing colorectal anastomosis. The results were assessed radiologically by barium studies on the tenth postoperative day. There was no significant difference in the incidence of anastomotic breakdown with either technique when the anastomosis was performed above the pelvic peritoneal reflection. When the anastomosis was situated below the pelvic peritoneum the incidence of dehiscence was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
2
7

Year Published

1979
1979
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(33 citation statements)
references
References 6 publications
1
23
2
7
Order By: Relevance
“…One RCT 51 matched the inclusion criteria, showing no significant differences in AL between single-and double-layer colorectal anastomosis in 92 patients. This RCT conducted a subgroup analysis of 25 low colorectal anastomoses, finding a significantly higher incidence of AL in colorectal anastomosis created with the double-layer technique.…”
Section: Single-vs Double-layer Colorectal Anastomosismentioning
confidence: 99%
“…One RCT 51 matched the inclusion criteria, showing no significant differences in AL between single-and double-layer colorectal anastomosis in 92 patients. This RCT conducted a subgroup analysis of 25 low colorectal anastomoses, finding a significantly higher incidence of AL in colorectal anastomosis created with the double-layer technique.…”
Section: Single-vs Double-layer Colorectal Anastomosismentioning
confidence: 99%
“…Other advocates of a singlelayer method have included Gambee et al (1956), Matheson & Irving (1975) and Sharma (1977). Controlled trials by and Goligher et al (1977) revealed little difference between one-and two-layer techniques, but Everett (1975) had only one breakdown in I I low anterior resections sutured in one layer, compared with 7 out of 14 when two layers were used.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the differences in technique account, at least partly, for differences in reported leakage rates. For example Everett (1975) as well as Goligher et al (1977) used interrupted stitches that traversed the full thickness of the bowel wall including the mucosa. On the other hand, Matheson & Irving (1975) used 3"0" braided nylon sutures that traversed all the layers of the intestine except the mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the clinical use of a single-layer method in rectal anastomosis has seldom been reported. A notable contribution on this subject was the report by Everett (1975) ofa controlled clinical trial contrasting single-layer with the traditional two-layer technique of suture for 'high' as well as 'low' rectal anastomosis. He found no difference in the incidence of dehiscence between the one and two-layer techniques of suture after 'high' anastomosis, but a significantly lower incidence after the one-layer technique for 'low' anastomosis.…”
Section: Introductionmentioning
confidence: 99%